Human adenovirus species C recombinant virus continuously circulated in China - Jianfang Yang (Nature Portfolio, 2019)
Abstract To date, at least three lineages (Lineage 1–3) that are related to recombinant human adenovirus species C (HAdV-C) have been identified in China. Among them, Lineage 1 includes two Chinese strains, strain KR699642-CHN-20093 (CBJ11) and strain MF315029-CHN-2013 (BJ09), which were collected in Beijing in 2009 and 2013, respectively. Herein, we performed genomic and bioinformatics analysis of two HAdV-C strains (strain SX-2000-140 and strain SX-2004-327) that were isolated from the feces of two healthy children in Shanxi province of China in 2000 and 2004, respectively. Results revealed that the genomes of both Shanxi strains had the highest homology to two Chinese HAdV-C strains belonging to Lineage 1 and harbored the genetic elements of these two strains, thereby presuming that Lineage1 has been circulated in mainland of China for decades. In addition, though the viruses in Lineage 1 showed slightly different recombinant patterns resulting from the recombinant events among the five types of HAdV-C, all the Lineage 1 viruses shared the highest sequence similarities with the HAdV-2 prototype strain (NC_001405-USA-1953) across the genome, especially in the major capsid genes including hexon, and fiber. These results indicated that Lineage 1 viruses that were associated with recombinants shared a common ancestor that is closely related to the HAdV-2 virus. Our current findings confirmed that frequent recombination among the different HAdV-C types might be an important driving force for the molecular evolution of HAdV-C. Therefore, there is a strong need for further comprehensive and systematic monitoring, detection, and research on HAdV-C.